Synthesis and Cation Binding Properties of p-Tert-butyl-calix[4]arene Bearing 8-Hydroxyquinoline Units - Mannai, Slim; Kim, Yang; Al-Ayed, Abdullah S.; Baklouti, Lassaad; Hamdi, Abdelwaheb (Letters in Organic Chemistry, 2018)
We report the synthesis and complexation properties of two new hydroxyquinolinecalixarene derivatives 1 and 2. The complexation studies of the synthesized ligands toward lanthanide cations have been monitored by UV absorption spectrophotometry and conductimetric in acetonitrile. The extraction properties into water to dichloromethane of 1 and 2 toward La(III), Gd(III) and Yb(III) have been also determined.
Keywords: extraction